Spectral and temporal signatures of ultrarelativistic protons in compact sources. I. Effects of Bethe-Heitler pair production - Mastichiadis, A.; Protheroe, R. J.; Kirk, J. G. (2005)
We present calculations of the spectral and temporal radiative signatures expected from ultrarelativistic protons in compact sources. The coupling between the protons and the leptonic component is assumed to occur via Bethe-Heitler pair production. This process is treated by modeling the results of Monte-Carlo simulations and incorporating them in a time-dependent kinetic equation, that we subsequently solve numerically. Thus, the present work is, in many respects, an extension of the leptonic “one-zone” models to include hadrons. Several examples of astrophysical importance are presented, such as the signature resulting from the cooling of relativistic protons on an external black-body field and that of their cooling in the presence of radiation from injected electrons. We also investigate and refine the threshold conditions for the “Pair Production/Synchrotron” feedback loop which operates when relativistic protons cool efficiently on the synchrotron radiation of the internally produced Bethe-Heitler pairs. We demonstrate that an additional component of injected electrons lowers the threshold for this instability.
Keywords: Active; Astrophysics; galaxies; radiation mechanisms: non-thermal; radiative transfer